Ознаки и награди на цивилната заштита на СФРЈ - Insignia and Awards of the Civil Protection Organization of SFRY - Trajce Trajkov (Македонски хералд - Macedonian Herald, 2023)
The article describes the insignia of the Civil Protection organization of the Socialist Federative Republic of Yugoslavia (SFRY), namely: emblem, general ensign, insignia of specialized units, insignia of functions in civil protection units and insignia of functions in civil protection headquarters, as well as awards - a plaque and civil protection pin. In addition, the plaque and badge of the Center for Civil Protection of the Federal Secretariat for People’s Defense (FSPD) are presented, as well as the republican awards for civil protection of the Socialist Republic (SR) of Croatia - gold, silver and bronze medals, gold badge and recognition, which were unique of that kind in former Yugoslavia. Special emphasis is placed on the international civil protection sign, legally standardized in acts of international humanitarian law, which forms the basis for the design of the signs of civil protection in most countries in the world.It is an interesting and under-researched topic, especially in terms of signumanistics and uniformology, as well of phaleristics, and then especially in a Macedonian context given that a large number of Macedonian citizens, organizations and institutions were awarded with the plaque and badge of civil protection of SFRY.